Core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for sodium battery, preparation method of negative electrode material and working electrode

The core-shell hard and soft interwoven carbon layer coats the metal oxide negative electrode material, which solves the problems of poor conductivity and pulverization in sodium batteries, improves sodium storage capacity and cycle stability, simplifies the preparation process and reduces costs. Suitable for industrial applications.

CN119297223APending Publication Date: 2025-01-10CHONGQING JIAOTONG UNIV +1

Patent Information

Application Number
CN202411306374.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing sodium battery negative electrode materials have problems such as poor conductivity and pulverization, and the theoretical sodium storage capacity of carbon-based materials is not high enough to meet the needs of sodium batteries.

Method used

The hard and soft interwoven carbon layer is used to coat the metal oxide negative electrode material. Through the combination of asphalt materials, hard carbon precursors and metal oxide precursors, a hard and soft interwoven carbon layer is formed to coat the metal oxide and improve conductivity. Sex and stability.

Benefits of technology

It has achieved improvements in conductivity, sodium storage capacity and cycle stability, reduced the risk of powdering of electrodes, simplified the preparation process, reduced costs, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049338270000151
    Figure BDA0005049338270000151
  • Figure BDA0005049338270000161
    Figure BDA0005049338270000161
  • Figure HDA0005049338280000011
    Figure HDA0005049338280000011
Patent Text Reader

Abstract

The invention provides a sodium battery core-shell type hard and soft interwoven carbon layer coated metal oxide negative electrode material, which is prepared from the following raw materials: an asphalt material, a hard carbon precursor, a metal oxide precursor and template salt, and the mass ratio of the asphalt material to the hard carbon precursor to the metal oxide precursor to the template salt is 1: (0.5-2): (1-2): 4; the core-shell type negative electrode material comprises a metal oxide and a hard-soft interwoven carbon layer coated on the surface of the metal oxide. On the other hand, the invention also provides a preparation method of the core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for the sodium battery, namely a one-step pyrolysis method. The problems that in the prior art, the defect that a metal oxide negative electrode is prone to pulverization or poor in conductivity can only be singly improved, and meanwhile, the formula is complex, the cost is high or the environment is polluted are solved, the defects that the electrode is prone to pulverization and poor in conductivity are synchronously improved, and the service life of the electrode is prolonged. And the performance of the electrode is improved to the maximum extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for sodium batteries, and in particular to a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for sodium batteries, a preparation method thereof, and a working electrode. Background Art

[0002] The application of carbon-based materials in battery negative electrode materials has been relatively mature, and they also have great potential in the development of negative electrode materials for sodium batteries; among them, soft carbon and hard carbon are regarded as the most promising carbonaceous materials for sodium battery negative electrodes due to their environmental friendliness, low price and adjustable interlayer spacing. Specifically, soft carbon has a relatively orderly arrangement, high crystallinity, few defects, good conductivity (high conductivity), and can withstand the charge and discharge process under high current density and has good rate performance, but its sodium storage capacity is low. In contrast to soft carbon, hard carbon is composed of randomly oriented vortex carbon layers, with a highly disordered structure, large interlayer distance, many defects, and a large specific surface area, which is beneficial to the diffusion of sodium ions. This structural diversity provides a large number of storage sites to achieve high sodium storage capacity; however, hard carbon also exhibits poor conductivity (low conductivity) due to the lack of long-range ordered crystal structure and the discontinuous transmission path of electrons inside it. It can be seen that there are still major deficiencies in the application of hard carbon and soft carbon in the negative electrode materials of sodium batteries, and the theoretical sodium storage capacity of carbon-based materials is still not high enough to meet the needs of sodium batteries.

[0003] In recent years, compared with carbon-based materials, metal oxide negative electrode materials have rapidly entered people's field of vision due to their higher theoretical sodium storage capacity. However, metal oxides still have some shortcomings as negative electrode materials. On the one hand, their own electrical conductivity is poor; on the other hand, their volume will undergo huge changes during the sodium ion insertion and extraction process (metal oxides will undergo chemical changes during the charging and discharging process to generate other substances, resulting in a large change in volume), that is, they will have excessive expansion and contraction during the charging and discharging process, which can easily lead to the pulverization of the electrode. The performance of the material will also become worse and worse or even fail, especially the rate performance and cycle stability of the electrode are not ideal, and still cannot meet the needs of practical applications. The existing technology mostly uses carbon-based materials to coat them to improve the conductivity or easy pulverization defects of metal oxide electrodes, for example:

[0004] Patent CN118270826A discloses a method for preparing a CuO / RGO porous carbon composite electrode material, which utilizes RGO to composite CuO to prepare the electrode material. Although the conductivity is improved due to the effect of RGO, on the one hand, graphene is expensive, which seriously increases the preparation cost and is not conducive to industrialization; on the other hand, in order to obtain larger active sites, terephthalic acid needs to be additionally used as a modifier, which further increases the complexity and cost of the formula.

[0005] Patent CN111153448A discloses a method for preparing and applying bamboo / wood-based nanocellulose confined transition metal oxide electrode materials, which uses carbon composite metal oxides derived from bamboo / wood-based cellulose to prepare electrode materials. Specifically, by taking advantage of the structure of cellulose itself, the transition metal oxides are directly confined in the network structure formed by bamboo / wood-based nanocellulose to make the two evenly and firmly combined, so that the electrode active material can maintain a stable morphology and structure during the electrochemical reaction. However, bamboo / wood-based cellulose is a recognized hard carbon precursor, which is difficult to graphitize, and the derived carbon has poor conductivity, which cannot improve the problem of poor conductivity of the metal oxide itself.

[0006] Patent CN117374254A discloses a silicon-carbon composite electrode material, which uses dextran as a hard carbon precursor to coat silicon nanoparticles with ultra-high capacity to buffer its volume expansion to optimize electrode performance. Specifically, a three-dimensional porous carbon skeleton is prepared by oxidizing dextran to cross-link collagen as a carrier of silicon, thereby obtaining a silicon-carbon composite material with a three-dimensional porous structure. The three-dimensional porous structure reserves space for the volume expansion of silicon, prevents the expansion from causing pulverization and damage to the material, and provides a large number of channels for the diffusion of lithium ions. Although this coated three-dimensional porous structure provides a good idea for improving the electrode pulverization phenomenon, on the one hand, a strong oxidant needs to be used in the preparation process to polymerize glucose, causing environmental pollution; on the other hand, the carbon material in the raw material is only the hard carbon precursor dextran, which is still insufficient to improve the conductivity of the silicon electrode; and finally, the collagen in the raw material only plays the role of a skeleton and cannot improve the conductivity of the silicon electrode.

[0007] Therefore, the carbon-based composite metal oxide negative electrode material prepared by the above-mentioned prior art can only be improved in a single way when improving the defects of easy pulverization or poor conductivity of the metal oxide negative electrode, and also faces the problems of complex formula, high cost or environmental pollution, and urgently needs to be improved. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for a sodium battery, which solves the problem that the prior art can only improve the defects of easy pulverization or poor conductivity of the metal oxide negative electrode in a single way, and at the same time faces the problems of complex formula, high cost or environmental pollution.

[0009] According to an embodiment of the present invention, a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material for a sodium battery, the raw materials used include an asphalt material, a hard carbon precursor, a metal oxide precursor and a template salt, and the mass ratio of asphalt material: hard carbon precursor: metal oxide precursor: template salt is 1:(0.5~2):(1~2):4; the core-shell type negative electrode material includes a metal oxide and a hard-soft interwoven carbon layer coated on the surface of the metal oxide.

[0010] On the other hand, according to an embodiment of the present invention, a method for preparing a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for a sodium battery is also provided, which comprises the following steps:

[0011] S1, dissolving the asphalt material in a solvent to obtain a black solution;

[0012] S2, uniformly mixing a hard carbon precursor, a metal oxide precursor and a template salt, and adding the mixture to the black solution, stirring the mixture for a period of time, and then removing the solvent to obtain a pre-processed base material;

[0013] S3, placing the obtained pre-processed bottom material in a tube furnace under a nitrogen atmosphere for high-temperature carbonization treatment to obtain a one-step pyrolysis product;

[0014] S4, washing the obtained one-step pyrolysis product with water to remove the template salt, and then drying it to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material.

[0015] On the other hand, according to an embodiment of the present invention, there is also provided a working electrode, which includes the core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material for a sodium battery.

[0016] The technical principle of the present invention is:

[0017] Asphalt-based materials are soft carbon precursors. Under the action of template salts, they form hard-soft interwoven carbon sheets with hard carbon precursors and encapsulate metal oxides inside, forming a core-shell structure with hard-soft interwoven carbon layers as shells and metal oxides as cores. On the one hand, the carbon shell layer can exert constraints on the metal oxides to alleviate their volume expansion, thereby improving their shortcomings of easy pulverization; on the other hand, the interwoven soft and hard carbon domains in the carbon shell layer have naturally complementary electrochemical properties, and can have moderate defects and interlayer spacing, large specific surface area, and excellent electrical conductivity and rate performance without the use of any external modifiers, thereby further improving the electrical conductivity, rate performance and sodium storage capacity of the composite material. Ultimately, the soft and hard interwoven carbon layers can simultaneously improve the conductivity, rate performance and cycle stability of the metal oxides to maximize the improvement of electrode performance.

[0018] In addition, the appropriate ratio of soft and hard carbon sources, on the one hand, enables the shell structure to maximize the combined advantages of soft and hard carbon. The hard carbon provides a larger specific surface area and interlayer spacing as well as abundant defects, which can respectively provide a faster sodium ion diffusion rate and a larger sodium storage capacity, while the soft carbon makes the structure more stable while improving the conductivity of the composite material. On the other hand, it ensures that the carbon shell has uniformly dispersed interwoven soft and hard carbon domains. Combined with the advantages of the above-mentioned hard and soft carbons, the structural stability, conductivity and sodium storage sites of each part of the carbon shell are improved, thereby improving the overall electrochemical performance of the composite electrode.

[0019] Finally, the appropriate ratio of metal oxide precursors leads to the appropriate metal oxide loading, and the appropriate metal oxide loading can take into account both good coating effect and high capacity. Although the capacity is high when the oxide content is too high, the coating effect is poor, and the electrode will still be pulverized during the cyclic charge and discharge process; although the electrode has good conductivity, cycle stability and rate performance when the oxide content is low, the capacity is low, which loses the meaning of composite metal oxides.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The defects of easy pulverization and poor conductivity are improved simultaneously. The use of a hard-soft interlaced carbon layer coating structure not only alleviates the problem of volume expansion of metal oxides and thus improves their easy pulverization defects, but also utilizes the structural stability of the hard-soft interlaced carbon layer and the naturally complementary electrochemical properties to further improve the conductivity, sodium storage capacity, cycle stability and rate performance of the metal oxide negative electrode, thereby maximizing the electrode performance.

[0022] 2. It has a good effect on improving electrode performance. The appropriate ratio of soft and hard carbon sources and metal oxide precursors allows the interwoven soft and hard carbon domains on the carbon shell to be evenly dispersed, making the carbon shell structure more stable. At the same time, it makes the metal oxide ratio in the electrode more appropriate, thus taking into account high capacity and good coating effect, and better exerting the comprehensive advantages of soft and hard carbon, and finally improving the overall electrochemical performance of the composite electrode.

[0023] 3. Simple formula, cheap and easy-to-obtain raw materials, green and environmentally friendly. First, there is no need to use external strong oxidants or other reagents as modifiers, the formula is simple and green and environmentally friendly; secondly, asphalt is an industrial by-product and is easy to graphitize, with good conductivity and rate performance, which is extremely economical and environmentally friendly compared to conductive agents such as graphene and conductive carbon black.

[0024] 4. The preparation method is simple. No strong oxidant or modifier is required for modification, nor is there any need for multiple carbonization treatments as in the preparation of a hard-soft double-layer coating structure. The hard-soft interwoven carbon layer coating structure can be obtained by only one-step pyrolysis, which is low-cost, controllable in process, and easy to industrialize.

[0025] 5. The working electrode has the above-mentioned advantages of the core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material of the present application.

[0026] Preferably, the asphalt material includes at least one of petroleum asphalt, coal asphalt and emulsified asphalt.

[0027] Beneficial effects: Asphalt is an industrial by-product, cheap, easy to obtain and economical; among them, emulsified asphalt can easily form a relatively stable water-emulsion liquid in water and is easy to mix.

[0028] Preferably, the hard carbon precursor includes one of glucose, sucrose, ice powder and starch.

[0029] Beneficial effects: Cheap and readily available, widely available, water-soluble, and easy to mix.

[0030] Preferably, the template salt includes NaCl, KCl, CaCl 2 、Na 2 CO 3 、Na 2 SO 4 and K 2 SO 4 One of the .

[0031] Beneficial effects: Cheap and all water-soluble templates can be removed by washing.

[0032] Preferably, the metal oxide precursor comprises ammonium ferric citrate, Co(NO 3 ) 2 6H 2 O、Co(CH 3 COO 2 、Fe(NO 3 ) 3 9H 2 O, FeCl 3 6H 2 O, Fe(OH)(CH 3 COO 2 、Mn(CH 3 COO 2 and Mn(NO 3 ) 2 6H 2 One of O.

[0033] Preferably, the metal oxide comprises Fe 2 O 3 , Fe 3 O 4 , CoO, Co 3 O 4 、MnO、Mn 2 O 3 and Mn 3 O 4 At least one of .

[0034] Beneficial effects: High sodium storage capacity.

[0035] Preferably, in step S1, when the asphalt material is petroleum asphalt and / or coal asphalt, the solvent includes trichloroethylene, and in terms of mL:g, trichloroethylene: asphalt material = (10-20):1; when the asphalt material is emulsified asphalt, the solvent includes deionized water.

[0036] Beneficial effects: Compared with solvents such as toluene, trichloroethylene is not a hazardous chemical and is more environmentally friendly.

[0037] Preferably, in step S3, the carbonization treatment conditions are: the heating rate is controlled at 2-10°C·min -1 , the carbonization temperature is 500-1000℃, and the insulation time is 1-3h. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a TEM image of pure hard carbon in the prior art.

[0039] Figure 2 This is a TEM image of pure soft carbon in the prior art.

[0040] Figure 3 This is the TEM image of the core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material prepared in Example 1.

[0041] Figure 4 for Figure 3 A partial enlarged view of .

[0042] Figure 5 for Figure 3 A partial enlarged view of . DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0044] 1. Description of the asphalt materials in the examples and comparative examples of the present application:

[0045] Petroleum asphalt grades include: AH-50, AH-70, AH-90, AH-110, AH-130, A-60, A-100, A-140, A-180, A-200; among which AH grade is mainly used for roads with heavy traffic, and A grade asphalt is used for roads with medium and light traffic (GB / T15180-2010);

[0046] Coal tar grades include: T-5, T-6, T-7, T-8, T-9;

[0047] Emulsified asphalt is prepared from petroleum asphalt or coal asphalt; the solid content of the emulsified asphalt used in this application is 60-65%, and its raw materials include: asphalt, water, emulsifier, stabilizer, special additives, modifier, etc.

[0048] The various grades of asphalt listed above can be selected for use in the embodiments and comparative examples of the present application; specifically, the main principle for selecting asphalt in Examples 1 to 15 of the present application and Comparative Examples 1 to 10 is: select petroleum asphalt and coal asphalt with grades of AH-50, AH-90, AH-130, A-200, T-5, T-7, and T-9 according to the asphaltene content in the asphalt; emulsified asphalt prepared from AH-70, AH-50, and A-200 petroleum asphalt is randomly selected because the emulsified asphalt is water-soluble (here it is actually easy to form a relatively stable aqueous emulsion in water) and the preparation process is similar.

[0049] 2. All drugs used in the experiment (template salt, etc.) were of analytical grade.

[0050] 3. Ammonium ferric citrate, molecular formula (NH 4 ) x Fe y (C 6 H 4 O 7 ) z .

[0051] Example 1

[0052] A method for preparing a working electrode comprises the following steps:

[0053] S1, 1 g of emulsified asphalt prepared from AH-70 petroleum asphalt was dispersed in 5 mL of deionized water to obtain a black solution;

[0054] S2, dissolving 1g glucose, 1.5g ammonium ferric citrate and 4g NaCl in 10mL deionized water, stirring evenly, and then adding to the above black solution, stirring continuously for 30min, and then freeze-drying to obtain a powdered pre-processed base material;

[0055] S3, put the powdered pre-processed base material into a crucible, then place the crucible in a tube furnace, and calcine at 1000°C for 1 hour under a nitrogen atmosphere, with a heating rate of 5°C·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0056] S4, the obtained one-step pyrolysis product is washed with deionized water to remove the template salt, and then placed in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material (such as Figure 3-Figure 5 As shown; among them, Figure 3 The overall core-shell hard-soft interwoven carbon layer coating structure is demonstrated; Figure 4 and Figure 5 The soft and hard carbon domains are marked respectively in the figure, and the interweaving effect of the soft and hard carbon domains is shown);

[0057] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0058] Example 2

[0059] A method for preparing a working electrode comprises the following steps:

[0060] S1, 1 g of emulsified asphalt prepared from AH-50 petroleum asphalt was dispersed in 5 mL of deionized water to obtain a black solution;

[0061] S2, 1g glucose, 1.5g Co(CH 3 COO 2 and 4 g NaCl were dissolved in 10 mL deionized water and stirred evenly, then added to the above black solution, and stirred for 30 min, and then freeze-dried to obtain a powdered pre-processed base material;

[0062] S3, put the above powdered pre-processed base material into a crucible, then place the crucible in a tube furnace, and calcine at 900°C for 1h under a nitrogen atmosphere with a heating rate of 5°C·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0063] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0064] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0065] Example 3

[0066] A method for preparing a working electrode comprises the following steps:

[0067] S1, weigh 1g T-5 coal tar pitch and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0068] S2, 1g glucose, 1.5g Fe(NO 3 ) 3 9H 2 O and 4g KCl were fully ground in an agate mortar for 10 minutes, then added to the above black solution, and stirred continuously for 30 minutes to obtain a uniform mixture, and then the mixture was added to an oil bath pot, and the temperature of the oil bath pot was set to 110°C, and trichloroethylene was distilled and condensed to recover under continuous stirring to obtain a pre-processed base material;

[0069] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 900℃ for 1h under nitrogen atmosphere, with a heating rate of 2℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0070] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0071] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0072] Example 4

[0073] A method for preparing a working electrode comprises the following steps:

[0074] S1, weigh 1g A-200 petroleum asphalt and dissolve it in 15ml trichloroethylene to obtain a black solution;

[0075] S2, 1g ice powder, 1.5g Fe(OH)(CH 3 COO 2 and 4 g of NaCl were fully ground in an agate mortar for 10 minutes, then added to the above black solution, and stirred continuously for 30 minutes to obtain a uniform mixture, and then the mixture was added to an oil bath pot, and the temperature of the oil bath pot was set to 100° C., and trichloroethylene was distilled and condensed to recover trichloroethylene under continuous stirring to obtain a pre-processed base material;

[0076] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 750℃ for 1h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0077] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0078] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 20 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil, placed in a vacuum drying oven at 70°C for 10 hours to obtain a working electrode.

[0079] Example 5

[0080] A method for preparing a working electrode comprises the following steps:

[0081] S1, 1 g of emulsified asphalt prepared from A-200 petroleum asphalt was dispersed in 5 mL of deionized water to obtain a black solution;

[0082] S2, 1g sucrose, 2g Mn(CH 3 COO 2 and 4 g CaCl 2 All of them were dissolved in 10 mL of deionized water and stirred evenly, then added to the above black solution, and stirred continuously for 30 min, and then freeze-dried to obtain a powdered pre-processed base material;

[0083] S3, put the powdered pre-processed base material into a crucible, then place the crucible in a tube furnace, and calcine at 800°C for 2h under a nitrogen atmosphere at a heating rate of 5°C·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0084] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 70° C. for 11 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0085] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 10 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven for drying at 80°C for 8 hours to obtain a working electrode.

[0086] Example 6

[0087] A method for preparing a working electrode comprises the following steps:

[0088] S1, weigh 1g AH-90 petroleum asphalt and dissolve it in 20ml trichloroethylene to obtain a black solution;

[0089] S2, 1g starch, 1g Co(NO 3 ) 2 6H 2 O and 4g NaCl were fully ground in an agate mortar for 10 minutes, then added to the above black solution, and stirred continuously for 30 minutes to obtain a uniform mixture, and then the mixture was added to an oil bath pot, and the temperature of the oil bath pot was set to 120°C, and trichloroethylene was distilled and condensed to recover under continuous stirring to obtain a pre-processed base material;

[0090] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 1000℃ for 1h under nitrogen atmosphere, with a heating rate of 2℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0091] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 80° C. for 10 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0092] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0093] Example 7

[0094] A method for preparing a working electrode comprises the following steps:

[0095] S1, weigh 1g AH-50 petroleum asphalt and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0096] S2, 1g sucrose, 1g Co(NO 3 ) 2 6H 2 O and 4g Na 2 SO 4 After being fully ground in an agate mortar for 10 minutes, the mixture is added to the above black solution, and the mixture is continuously stirred for 30 minutes to obtain a uniform mixture. The mixture is then added to an oil bath pot, and the temperature of the oil bath pot is set to 130° C., and trichloroethylene is recovered by distillation and condensation under continuous stirring to obtain a pre-processed base material;

[0097] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 800℃ for 1h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0098] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 80° C. for 9 hours to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0099] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 7:2:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0100] Example 8

[0101] A method for preparing a working electrode comprises the following steps:

[0102] S1, weigh 1g T-9 coal tar pitch and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0103] S2, 1g sucrose, 1g FeCl 3 6H 2 O and 4g Na 2 CO 3After being fully ground in an agate mortar for 10 minutes, the mixture is added to the above black solution, and the mixture is continuously stirred for 30 minutes to obtain a uniform mixture. The mixture is then added to an oil bath pot, and the temperature of the oil bath pot is set to 140° C., and trichloroethylene is recovered by distillation and condensation under continuous stirring to obtain a pre-processed base material;

[0104] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 800℃ for 1h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0105] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 80° C. for 8 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0106] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 7:2:1 to form a uniform slurry, and then the slurry is coated on a copper foil, placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0107] Example 9

[0108] A method for preparing a working electrode comprises the following steps:

[0109] S1, weigh 1g A-100 petroleum asphalt and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0110] S2, 0.5 g sucrose, 1 g FeCl 3 6H 2 O and 4g NaCl were fully ground in an agate mortar for 10 minutes, then added to the above black solution, and stirred continuously for 40 minutes to obtain a uniform mixture, and then the mixture was added to an oil bath pot, and the temperature of the oil bath pot was set to 150°C, and trichloroethylene was distilled and condensed to recover under continuous stirring to obtain a pre-processed base material;

[0111] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 600℃ for 3h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0112] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0113] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0114] Example 10

[0115] A method for preparing a working electrode comprises the following steps:

[0116] S1, 1 g of emulsified asphalt prepared from AH-70 petroleum asphalt was dispersed in 5 mL of deionized water to obtain a black solution;

[0117] S2, 0.5 g glucose, 1.5 g ammonium ferric citrate and 4 g NaCl were dissolved in 10 mL deionized water and stirred evenly, then added to the above black solution, and stirred continuously for 50 min, and then freeze-dried to obtain a powdered pre-processed base material;

[0118] S3, put the powdered pre-processed base material into a crucible, then place the crucible in a tube furnace, and calcine at 1000°C for 1 hour under a nitrogen atmosphere, with a heating rate of 5°C·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0119] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0120] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and sodium alginate (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: sodium alginate = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0121] Embodiment 11

[0122] A method for preparing a working electrode comprises the following steps:

[0123] S1, weigh 1g T-6 coal tar pitch and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0124] S2, 0.5g glucose, 1g ammonium ferric citrate and 4g Na 2 CO 3 After being fully ground in an agate mortar for 10 minutes, the mixture is added to the above black solution, and the mixture is continuously stirred for 60 minutes to obtain a uniform mixture. The mixture is then added to an oil bath pot, and the temperature of the oil bath pot is set to 110° C., and trichloroethylene is recovered by distillation and condensation under continuous stirring to obtain a pre-processed base material;

[0125] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 700℃ for 3h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0126] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0127] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0128] Example 12

[0129] A method for preparing a working electrode comprises the following steps:

[0130] S1, weigh 1g AH-130 petroleum asphalt and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0131] S2, 2g sucrose, 1g Mn(NO 3 ) 2 6H 2 O and 4g NaCl were fully ground in an agate mortar for 10 minutes, then added to the above black solution, and stirred continuously for 30 minutes to obtain a uniform mixture, and then the mixture was added to an oil bath pot, and the temperature of the oil bath pot was set to 110°C, and trichloroethylene was distilled and condensed to recover under continuous stirring to obtain a pre-processed base material;

[0132] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 800℃ for 1h under nitrogen atmosphere, with a heating rate of 10℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0133] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0134] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 7:2:1 to form a uniform slurry, and then the slurry is coated on a copper foil, placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0135] Example 13

[0136] A method for preparing a working electrode comprises the following steps:

[0137] S1, weigh 1g T-7 coal tar and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0138] S2, 2g sucrose, 1g Mn(NO 3 ) 2 6H 2 O and 4g K 2 SO 4 After being fully ground in an agate mortar for 10 minutes, the mixture is added to the above black solution, and the mixture is continuously stirred for 30 minutes to obtain a uniform mixture. The mixture is then added to an oil bath pot, and the temperature of the oil bath pot is set to 110° C., and trichloroethylene is recovered by distillation and condensation under continuous stirring to obtain a pre-processed base material;

[0139] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 500℃ for 3h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0140] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0141] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 7:2:1 to form a uniform slurry, and then the slurry is coated on a copper foil, placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0142] Embodiment 14

[0143] A method for preparing a working electrode comprises the following steps:

[0144] S1, weigh 1g T-7 coal tar and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0145] S2, 2g ice powder, 1.5g Mn(NO 3 ) 2 6H 2 O and 4g K 2 SO 4 After being fully ground in an agate mortar for 10 minutes, the mixture is added to the above black solution, and the mixture is continuously stirred for 30 minutes to obtain a uniform mixture. The mixture is then added to an oil bath pot, and the temperature of the oil bath pot is set to 110° C., and trichloroethylene is recovered by distillation and condensation under continuous stirring to obtain a pre-processed base material;

[0146] S3, put the obtained pre-processed bottom material into a crucible, then place the crucible in a tube furnace, and calcine at 500℃ for 3h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0147] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0148] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 7:2:1 to form a uniform slurry, and then the slurry is coated on a copper foil, placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0149] Embodiment 15

[0150] A method for preparing a working electrode comprises the following steps:

[0151] S1, weigh 1g T-8 coal tar pitch and dissolve it in 10ml trichloroethylene to obtain a black solution;

[0152] S2, 2g glucose, 2g Mn(CH 3 COO 2 and 4g Na 2 SO 4 After being fully ground in an agate mortar for 10 minutes, the mixture is added to the above black solution, and the mixture is continuously stirred for 30 minutes to obtain a uniform mixture. The mixture is then added to an oil bath pot, and the temperature of the oil bath pot is set to 110° C., and trichloroethylene is recovered by distillation and condensation under continuous stirring to obtain a pre-processed base material;

[0153] S3, put the obtained pre-processed bottom material into a crucible, and then place the crucible in a tube furnace, and calcine it at 850℃ for 1h under nitrogen atmosphere, with a heating rate of 5℃·min -1 ; After naturally cooling to room temperature, a one-step pyrolysis product is obtained;

[0154] S4, washing the obtained one-step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material;

[0155] S5, the obtained core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material, conductive agent Super P and polyvinylidene fluoride (as a binder) are mixed and ground for 30 minutes in a mass ratio of metal oxide negative electrode material: conductive agent Super P: polyvinylidene fluoride = 8:1:1 to form a uniform slurry, and then the slurry is coated on a copper foil and placed in a vacuum drying oven at 60°C for 12 hours to obtain a working electrode.

[0156] Comparative Example 1

[0157] The difference from Example 1 is that glucose is not added in step S2.

[0158] Comparative Example 2

[0159] The difference from Example 1 is that in step S1, emulsified asphalt prepared from AH-70 petroleum asphalt is not added, in step S2, 1 g of glucose, 1.5 g of ammonium ferric citrate and 4 g of NaCl are all dissolved in 10 mL of deionized water and stirred evenly before being directly added to 5 mL of deionized water, and the subsequent steps are the same as in Example 1.

[0160] Comparative Example 3

[0161] The difference from Example 1 is that 0.4 g of glucose is added in step S2.

[0162] Comparative Example 4

[0163] The difference from Example 1 is that 0.4 g of emulsified asphalt prepared from AH-70 petroleum asphalt is added in step S1.

[0164] Comparative Example 5

[0165] The difference from Example 1 is that 3 g of emulsified asphalt prepared from AH-70 petroleum asphalt is added in step S1.

[0166] Comparative Example 6

[0167] The difference from Example 1 is that 3.5 g of glucose is added in step S2.

[0168] Comparative Example 7

[0169] The difference from Example 1 is that 3 g of ammonium ferric citrate is added in step S2.

[0170] Comparative Example 8

[0171] The difference from Example 1 is that 0.5 g of ammonium ferric citrate is added in step S2.

[0172] Comparative Example 9

[0173] The main difference from Example 1 is that the structure of the prepared core-shell metal oxide negative electrode material is different, which is a hard-soft double-layer coating structure, from the inside to the outside are metal oxide, soft carbon, hard carbon, that is, the outermost layer is hard carbon.

[0174] The preparation steps of the core-shell type hard-soft double-layer coated metal oxide negative electrode material (the outermost layer is hard carbon) are as follows:

[0175] T1, 1 g of emulsified asphalt prepared from AH-70 petroleum asphalt was dispersed in 5 mL of deionized water to obtain a black solution;

[0176] T2, dissolving 1.5 g of ammonium ferric citrate and 2 g of NaCl in 10 mL of deionized water, stirring evenly, and then adding the mixture to the above black solution, stirring continuously for 30 min, and then freeze-drying to obtain a powdered first pre-processed base material;

[0177] T3, put the powdered first pre-processed base material into a crucible, then place the crucible in a tube furnace, and calcine at 500°C for 30 min in a nitrogen atmosphere with a heating rate of 5°C·min -1 ; Then naturally cool to room temperature to obtain the first step pyrolysis product;

[0178] T4, washing the first step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain a black powder;

[0179] T5, 1 g of glucose and 2 g of NaCl were dissolved in 10 mL of deionized water, and then the obtained black powder was added thereto, and ultrasonic dispersion was performed for 30 min, and then freeze-dried to obtain a powdered second pre-processed base material;

[0180] T6, put the powdered second pre-processed base material into a crucible, and then place the crucible in a tube furnace, and calcine at 1000°C for 30 minutes under a nitrogen atmosphere, with a heating rate of 5°C·min -1 ; Then naturally cool to room temperature to obtain the second step pyrolysis product;

[0181] T7, the second step pyrolysis product is washed with deionized water to remove the template salt, and then placed in a vacuum drying oven at 60° C. for 12 h to obtain a core-shell type hard-soft double-layer coated metal oxide negative electrode material (the outermost layer is hard carbon).

[0182] Note that the method for preparing a working electrode from the core-shell type hard-soft double-layer coated metal oxide negative electrode material (the outermost layer is hard carbon) is the same as in Example 1 and will not be repeated here.

[0183] Comparative Example 10

[0184] Similarly, the main difference from Example 1 is that the structure of the prepared core-shell metal oxide negative electrode material is different, which is also a hard-soft double-layer coating structure, with metal oxide, hard carbon, and soft carbon from the inside to the outside, that is, the outermost layer is soft carbon.

[0185] The preparation steps of the core-shell type hard-soft double-layer coated metal oxide negative electrode material (the outermost layer is soft carbon) are as follows:

[0186] T1, 1 g of glucose was dissolved in 5 mL of deionized water to obtain a colorless and transparent solution;

[0187] T2, dissolving 1.5 g of ammonium ferric citrate and 2 g of NaCl in 10 mL of deionized water, stirring evenly, and then adding the mixture to the colorless transparent solution, stirring continuously for 30 min, and then freeze-drying to obtain a powdered first pre-processed base material;

[0188] T3, put the powdered first pre-processed base material into a crucible, then place the crucible in a tube furnace, and calcine at 500°C for 30 min in a nitrogen atmosphere with a heating rate of 5°C·min -1 ; Then naturally cool to room temperature to obtain the first step pyrolysis product;

[0189] T4, washing the first step pyrolysis product with deionized water to remove the template salt, and then drying it in a vacuum drying oven at 60°C for 12 hours to obtain a powdered sample;

[0190] T5, dissolving 1 g of emulsified asphalt prepared from AH-70 petroleum asphalt and 2 g of NaCl in 10 mL of deionized water to obtain a black solution, then adding the powdered sample obtained in the previous step, and then ultrasonically dispersing for 30 min, and then freeze-drying to obtain a powdered second pre-processed base material;

[0191] T6, put the powdered second pre-processed base material into a crucible, and then place the crucible in a tube furnace, and calcine at 1000°C for 30 minutes under a nitrogen atmosphere, with a heating rate of 5°C·min -1 ; Then naturally cool to room temperature to obtain the second step pyrolysis product;

[0192] T7, the second step pyrolysis product is washed with deionized water to remove the template salt, and then placed in a vacuum drying oven at 60°C for 12 hours to obtain a core-shell type hard-soft double-layer coated metal oxide negative electrode material (the outermost layer is soft carbon).

[0193] Note that similarly, the method for preparing a working electrode from the core-shell type hard-soft double-layer coated metal oxide negative electrode material (the outermost layer is soft carbon) is the same as in Example 1 and will not be repeated here.

[0194] Performance Testing

[0195] The prepared working electrode was used as the negative electrode, the sodium sheet as the counter electrode, the glass fiber as the diaphragm, and the electrolyte solute was 1 mol·L -1 NaClO 4 The solvent consisted of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and CR2032 button-type sodium-ion batteries were assembled in an argon-filled glove box.

[0196] CR2032 button sodium ion battery in the voltage range of 0.01 ~ 2.7V, 100mA·g -1 The electrochemical performance test was carried out at a current density of 1.5 Å, and the discharge specific capacity of the second cycle and the capacity retention rate (cycle performance) after 100 cycles were recorded and recorded in Table 1.

[0197] CR2032 button sodium ion battery in the voltage range of 0.01 ~ 2.7V, successively under 100mA·g -1 , 200mA·g -1 , 500mA·g -1 , 1000mA·g -1 , 2000mA·g -1 and 100mA·g -1 The electrochemical performance was tested by 10 cycles at each current density, and the first 100 mA g -1 The discharge capacity of the second cycle and the last 100mA·g -1The discharge specific capacity of the last cycle was calculated, and the capacity recovery rate (rate performance) was calculated and recorded in Table 1.

[0198] The above cycle and rate performance are completed by Xinwei battery testing system (T2110-291024).

[0199] In addition, the CHI660E electrochemical workstation of Shanghai Zhenhua Technology Co., Ltd. was used to perform AC impedance test to study the conductivity of the composite material. The AC amplitude was 5mV and the frequency was 0.01Hz~100kHz. The test results are recorded in Table 1.

[0200] Table 1 Performance test results of Examples 1 to 15 and Comparative Examples 1 to 10

[0201]

[0202]

[0203] Note: In Table 1, "soft" refers to asphalt-based materials, "hard" refers to hard carbon precursors, and "metal salts" refer to metal oxide precursors; the ratio in the "electrode" column refers to, by mass ratio, core-shell type hard and soft interwoven carbon layers coated with metal oxide negative electrode materials: conductive agent Super P: binder = 8:1:1 or 7:2:1.

[0204] Performance test results analysis

[0205] 1. Definitions of relevant terms and necessary explanations:

[0206] ①100mA·g -1 Discharge capacity (mAh g -1 ): Current density is 100 mA g -1 The second cycle discharge specific capacity at .

[0207] Note that the discharge capacity of the second cycle is used here and in the following concepts because the discharge capacity of the first cycle is generally unstable, with a large drop from the first cycle to the second cycle. The second cycle and thereafter are relatively stable because the SEI film must be formed in the first cycle and is irreversible, which consumes more sodium ions.

[0208] ②Capacity retention rate (%): Here refers to the current density of 100mA·g -1 , the discharge capacity of the 100th cycle / the discharge capacity of the second cycle.

[0209] ③Capacity recovery rate (%): After 100mA·g -1 , 200mA·g -1 , 500mA·g -1 , 1000mA·g -1 , 2000mA·g -1and 100mA·g -1 After 10 cycles at each current density, compare the relative size of the last cycle discharge capacity of the last 100 cycles with the second cycle discharge capacity of the first 100 cycles, that is, judge the rate performance of the electrode based on the capacity recovery. That is, capacity recovery rate = (last 100mA·g -1 The last cycle discharge capacity / the first 100mA·g -1 The second cycle discharge specific capacity under (the ...

[0210] ④ Transfer resistance (Ω): A resistance parameter used to describe the charge transfer process at the electrochemical cell or electrode interface, reflecting the transfer speed and efficiency of electrons between the electrode and the electrolyte.

[0211] 2. Results Analysis

[0212] (1) In each embodiment of the present application:

[0213] The transfer resistance values ​​are all around 300Ω, which is significantly lower than the transfer resistance value of a simple metal oxide electrode (around 500-700Ω), indicating that the conductivity of the electrode has been greatly improved.

[0214] 100mA·g -1 The capacity retention rates are all above 91%, and most of them have reached about 95%, indicating that under a certain current density, the discharge specific capacity of the electrode can still be maintained at a level close to the initial level (i.e., the level of the second cycle) after 100 cycles of charge and discharge, and the cycle stability is good; at the same time, the capacity recovery rate is mostly close to 100%, or even higher than 100%, and the minimum is not less than 96%, indicating that after multiple cycles of charge and discharge at high current density, the attenuation amplitude of the electrode discharge capacity is very small, and some even exceed the initial value due to electrode activation, which means that the rate performance of the electrode is also good. This proves that the core-shell structure of the hard and soft interwoven carbon layer coated metal oxide prepared in this application is relatively stable, and the coating effect is good, which effectively alleviates the problem of excessive volume expansion of metal oxides during the cyclic charge and discharge process, that is, it effectively improves the easy pulverization defect of the metal oxide electrode, so that the hard and soft interwoven carbon layer coating structure of this application has good cycle stability and rate performance.

[0215] (2) Analysis of transfer resistance value:

[0216] The transfer resistance value of Example 1 is 306Ω; compared with Example 1, the asphalt proportion of Comparative Example 4 is reduced (less than the optimal value range), the transfer resistance value is increased to 364Ω, and the conductivity is reduced; the asphalt content of Comparative Example 2 is reduced to 0 (the carbon shell layer only has hard carbon), the transfer resistance value is the highest, reaching 529Ω, and the conductivity is the worst; while the carbon shell raw material of Comparative Example 1 is only asphalt, the transfer resistance value is 286Ω, and the conductivity is even better than that of Example 1; when the asphalt proportion continues to increase to the level of Comparative Example 5, the transfer resistance value of the electrode continues to decrease to 279Ω, and the conductivity is further improved; Comparative Examples 9 and 10 are both hard-soft double-layer coating structures, and their asphalt proportions are the same as in Example 1, and the transfer resistance value is 513Ω when the outermost layer is hard carbon, and it is 298Ω when the outermost layer is soft carbon. It is explained that in the hard-soft interwoven carbon layer coating structure, asphalt contributes the most to the conductivity of the electrode, and within the asphalt ratio range of the present application, the conductivity of the electrode is good; once the asphalt ratio is less than this range, the conductivity of the electrode will deteriorate; and after the asphalt ratio increases, the electrode conductivity will also increase and even be better than Example 1; but considering the comprehensive performance, it is more appropriate to control the asphalt ratio within the scope of the present application. In addition, the transfer resistance value in the hard-soft double-layer coating structure is close to the corresponding transfer resistance value of only one pure soft or pure hard carbon shell layer, and since the transfer resistance value refers to the resistance in the outer layer of the material, it further illustrates that asphalt contributes the most to the conductivity of the electrode; furthermore, when the outermost layer of the hard-soft double-layer coating structure is soft carbon, although its conductivity is good, even better than the core-shell structure coated with the hard-soft interwoven carbon layer of the present application, its capacity recovery rate is small (92%), so considering the comprehensive performance, the electrode structure coated with the hard-soft interwoven carbon layer of the present application is more advantageous.

[0217] (3) About 100mA·g -1 Analysis of discharge specific capacity:

[0218] 100mA·g of Example 1 -1 The discharge capacity is 896 mAh g -1 Compared with Example 1, in Comparative Example 8, the proportion of metal oxide precursor is small (less than the optimal value range), and the discharge capacity is 301 mAh g -1 , the sodium storage capacity is small; while in Comparative Example 7, the metal oxide precursor accounts for a large proportion (greater than the optimal value range), and the discharge specific capacity is 965mAh·g -1, the sodium storage capacity is very high, which is better than Example 1, but its transfer resistance value is very large (456Ω), the capacity retention rate is very small (52%), and the capacity recovery rate is also very small (70%). This shows that the proportion of metal oxides in this application is more appropriate. If it is less than this range, the sodium storage capacity will be greatly reduced, and increasing its proportion will increase the sodium storage capacity, but considering the comprehensive performance, it is more appropriate to control it within the scope of this application. In addition, the discharge specific capacity of Comparative Examples 9 and 10 is also large, and both of them are hard-soft double-layer coating structures, but their capacity recovery rate is relatively small (92%). Therefore, considering the comprehensive performance, the electrode structure coated with hard and soft interwoven carbon layers in this application is more advantageous.

[0219] (4) Analysis of capacity retention rate and capacity recovery rate

[0220] The capacity recovery rate of Example 1 is 102%, and the capacity retention rate is 94%. Compared with Example 1, the carbon shell layer of Comparative Example 1 contains only soft carbon, and the capacity recovery rate is only 80%, the capacity retention rate is only 74%, and the rate performance and cycle stability are both poor, indicating that the effect of soft carbon alone on improving the rate performance is limited, and its coating effect is also poor, thereby alleviating the effect of volume expansion of the metal oxide electrode is also poor.

[0221] The carbon shell layer of Comparative Example 2 consists only of hard carbon, with a capacity recovery rate of 72% and a capacity retention rate of 76%. The rate performance is even worse and the cycle stability is still not good, indicating that the effect of hard carbon alone on improving the cycle stability is limited, and its coating effect is also poor. At the same time, it shows that soft carbon contributes more to improving the rate performance.

[0222] In Comparative Example 3, the proportion of hard carbon is relatively small (less than the optimal value range), which is equivalent to adding a small amount of hard carbon on the basis of Comparative Example 1. At the same time, the proportion of soft carbon decreases slightly, the capacity recovery rate is 76%, and the rate performance is slightly inferior to that of Comparative Example 1, further proving that soft carbon contributes more to improving the rate performance; the capacity retention rate of Comparative Example 3 is 93%, and the cycle stability is good, indicating that the hard carbon has a better effect on improving the cycle stability after being interwoven with the soft carbon, and also indicating that the hard-soft interwoven structure is more stable than the single hard carbon structure, which is more conducive to the hard carbon maintaining its advantage of high sodium storage capacity.

[0223] In Comparative Example 4, the proportion of soft carbon is small (less than the optimal value range), which is equivalent to adding a small amount of soft carbon on the basis of Comparative Example 2. The capacity recovery rate is 74%, which is slightly improved compared with Comparative Example 2 (72%), further indicating that soft carbon contributes more to improving rate performance; the capacity retention rate of Comparative Example 4 is 91%, which is close to Comparative Example 3, and the cycle stability is good or even better than Comparative Example 3, further indicating that increasing the proportion of hard carbon will also improve the cycle stability.

[0224] In Comparative Examples 5 and 6, the proportion of soft carbon and hard carbon is increased respectively, and the overall carbon content of the electrode material is also relatively large. The capacity recovery rate is 99%, and the capacity retention rate is 99% and 98% respectively. The rate performance and cycle stability are both good, indicating that the higher the carbon content, the better the coating effect, thereby alleviating the volume expansion of the metal oxide electrode, the better the structural stability, and the less prone to pulverization. However, the discharge specific capacity is relatively low, and the transfer resistance value of Comparative Example 6 is also relatively large. Therefore, considering comprehensively, it is more appropriate to control the proportion of soft and hard carbon within the scope of this application.

[0225] Comparative Examples 7 and 8 are cases where the proportion of metal oxide is high (greater than the optimal value range) and low (less than the optimal value range), respectively, and the carbon content of the corresponding electrodes is low and high, respectively, and their capacity recovery rates are 70% and 98%, respectively, and the capacity retention rates are 52% and 98%, respectively, further proving that the higher the carbon content, the better the coating effect. In addition, although Comparative Example 8 has good rate performance and cycle stability, its sodium storage capacity is small. Therefore, considering the comprehensive performance, it is more appropriate to control the proportion of metal oxide within the scope of this application.

[0226] Comparative Examples 9 and 10 are both hard-soft double-layer coating structures, with a capacity recovery rate of 92% and a capacity retention rate of 97% and 96% respectively. The corresponding cycle stability is good, but the rate performance is still insufficient, indicating that the hard-soft double-layer coating structure is not particularly stable, especially the stability of the hard carbon layer is poor. -1 It can remain relatively stable after multiple charge and discharge cycles, but it is easy to disintegrate after multiple charge and discharge cycles at high current density, so its rate performance is not good. This shows that the hard-soft double-layer coating structure is still insufficient in improving the rate performance of metal oxide electrodes, and the hard-soft interwoven carbon layer coating structure prepared in this application has a better effect on improving the rate performance of metal oxide electrodes; combined with the foregoing, it can be further known that the hard-soft interwoven carbon layer coating structure prepared in this application improves the electrode performance in all aspects, and it performs well in sodium storage capacity, conductivity, rate performance and cycle stability.

[0227] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for sodium battery, characterized in that: The raw materials used for the core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material include asphalt materials, hard carbon precursors, metal oxide precursors and template salts, and the mass ratio of asphalt materials: hard carbon precursors: metal oxide precursors: template salts is 1: (0.5-2): (1-2): 4; the core-shell type negative electrode material includes metal oxide and a hard-soft interwoven carbon layer coated on the surface of the metal oxide.

2. A sodium battery core-shell hard-soft interwoven carbon layer coated metal oxide negative electrode material as claimed in claim 1, characterized in that: The asphalt material includes at least one of petroleum asphalt, coal asphalt and emulsified asphalt.

3. A sodium battery core-shell hard-soft interwoven carbon layer coated metal oxide negative electrode material as claimed in claim 1, characterized in that: The hard carbon precursor includes one of glucose, sucrose, ice powder and starch.

4. A sodium battery core-shell hard-soft interwoven carbon layer coated metal oxide negative electrode material as claimed in claim 1, characterized in that: The template salt includes one of NaCl, KCl, CaCl2, Na2CO3, Na2SO4 and K2SO4.

5. A core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for sodium battery according to claim 1, characterized in that: The metal oxide precursor includes one of ammonium ferric citrate, Co(NO3)2·6H2O, Co(CH3COO)2, Fe(NO3)3·9H2O, FeCl3·6H2O, Fe(OH)(CH3COO)2, Mn(CH3COO)2 and Mn(NO3)2·6H2O.

6. A core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for sodium battery according to claim 1, characterized in that: The metal oxide includes at least one of Fe2O3, Fe3O4, CoO, Co3O4, MnO, Mn2O3 and Mn3O4.

7. A method for preparing a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for a sodium battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, dissolving the asphalt material in a solvent to obtain a black solution; S2, uniformly mixing a hard carbon precursor, a metal oxide precursor and a template salt, and adding the mixture to the black solution, stirring the mixture for a period of time, and then removing the solvent to obtain a pre-processed base material; S3, placing the obtained pre-processed bottom material in a tube furnace under a nitrogen atmosphere for high-temperature carbonization treatment to obtain a one-step pyrolysis product; S4, washing the obtained one-step pyrolysis product with water to remove the template salt, and then drying it to obtain a core-shell type hard-soft interwoven carbon layer-coated metal oxide negative electrode material.

8. The method for preparing a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for a sodium battery as claimed in claim 7, characterized in that: In step S1, when the asphalt material is petroleum asphalt and / or coal tar, the solvent includes trichloroethylene, and in terms of mL:g, trichloroethylene: asphalt material = (10-20):1; when the asphalt material is emulsified asphalt, the solvent includes deionized water.

9. The method for preparing a core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for a sodium battery as claimed in claim 7, characterized in that: In step S3, the carbonization treatment conditions are: the heating rate is controlled at 2-10°C·min -1 , the carbonization temperature is 500-1000℃, and the insulation time is 1-3h.

10. A working electrode, characterized in that: A core-shell type hard-soft interwoven carbon layer coated metal oxide negative electrode material for a sodium battery as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method and application of bamboo / wood-based nanocellulose confinement transition metal oxide electrode material

    CN111153448A

  • Silicon-carbon composite electrode material and preparation method and application thereof

    CN117374254A

Cited By

  • Negative electrode material for fast-charging lithium ion battery and preparation method of negative electrode material

    CN120308954A

  • Asphalt-based hard carbon negative electrode material and preparation method and application thereof

    CN120903472A